The cauldron has cooled down: a systematic literature review on home advantage in football during the COVID-19 pandemic from a socio-economic and psychological perspective - Leitner, M. C.; Daumann, F.; Follert, F.; Richlan, F. (Management Review Quarterly, 2023)
The phenomenon of home advantage (home bias) is well-analyzed in the scientific literature. But only the COVID-19 pandemic enabled studies on this phenomenon—for the first time in history—on a global scale. Thus, several studies to date examined the effects of empty stadiums by comparing regular matches (with supporters) before the COVID-19 restrictions with so-called ghost games (games without supporters) during the pandemic. To synthesize the existing knowledge and offer an overview regarding the effects of ghost games on home advantage we provide a systematic literature review on this topic. Our findings—based on 26 primary studies—indicate that ghost games have a considerable impact on the phenomenon of home advantage. Deeper analysis further indicates that this effect is based on a reduced "referee bias" and a lack of "emotional support from the ranks". From a psychological perspective, we argue that our conclusions are highly relevant by emphasizing decision making under pressure and crowd-induced motivation in sports. From a socio-economic perspective, we argue that our findings legitimize a discussion regarding compensation of fans after sporting success as plausible and worth considering. Thus, our results are significant for scientists, sports and team managers, media executives, fan representatives and other persons responsible in the football industry.